HOME CARE NURSES’ ROLES IN ENHANCING QUALITY OF NURSING CARE FOR PATIENTS AT HOME: A PHENOMENOLOGICAL STUDY - Titan Ligita (Belitung Raya Foundation, Indonesia, 2017)
Background: Provision of health care service at home is one of the advanced forms of care for patients being discharged from hospitalization. Little is known about the experience of nurses providing home care services through a nursing home-care model especially in Indonesian context. Objective: This study aims to explore the experience in order to increase understanding on the form of home care provision, and consequently the nurses may understand the form of home care globally. Methods: This study employed a phenomenological design and performed interview in the process of data collection. Data were analysed by using content analysis. Results: The main contexts of home care nurse experiences were generated. There were definition and role of home care nurses, the involvement of family members in the provision of care, the facilitating and hindering factors contributed to home care provision as well as manual on providing home care nursing. Conclusion: The implication from this study is that nursing care should be given to the patients continuously and consequently the need for family involvement is important. Additionally, in providing the home care, a proper manual is needed by home care nurses as the guidance to give best quality of care to patients.